P117 Pharmacy-led latent tb infection service: a success story. (15th November 2016) - Abunga, YO; Day, M; Brij, SO
Abstract : Introduction: Previously we have reported good outcomes following a pilot study of latent TB infection (LTBI) assessment and treatment by a dedicated TB Pharmacist. 1 Since that time, the service has been imbedded within our local practice to reduce waiting times, improve chemoprophylaxis adherence, enhance treatment outcomes, and minimise adverse drug reactions whilst maintaining a high standard of care. In addition, patients with more complex medical needs requiring biological therapy are now not excluded from this service. Aim: to review the safety and effectiveness of the Pharmacy-led Clinic Methods: Medical records of all cases of LTBI seen by the TB Pharmacist were reviewed retrospectively. Data obtained included patient demographics, treatment ± side-effects and clinical outcomes. Results: 206 patients with LTBI seen between Jan 2012 and December 2015 were identified (see Table 1 ). Contact tracing and the requirement for biological therapy were the commonest reasons for referral. 185 (89.8%) successfully completed treatment: 3 declined; 8 lost to follow up; 10 stopped due to side-effects. Significant drug side-effects included hepatitis, peripheral neuropathy, nausea and vomiting and only resulted in 2 non-completion, the rest were due to fatigue and headache. Of the 8 who stopped 1 developed active TB whilst on biological therapy. Patient satisfaction was good and patients would recommend this service to a friend or family member. Conclusion: The LTBI Pharmacy-led clinic has been successfully implemented and incorporated into our local TB practice with good outcomes. Keeping with the Carter Review, 2 it is important to utilise the skills and knowledge of previously unrecognised clinical partners to deliver high quality care. Patients were happy to be seen by the pharmacists. Poly pharmacy patients appreciated time spent to simplify regime and manage potential interaction. References: Abunga YO, Luwemba G, Brij SO. Diagnosis and management of TB: P59 Treatment and Drug Surveillance of Latent Tuberculosis Infections (LTBI) by a TB Pharmacist: A pilot study. Thorax 2012;67 (Suppl 2):A88. Department of Health. Independent report – Productivity in NHS hospitals [ONLINE]. https://www.gov.uk/government/uploads/system/uploads/attachment_data/file/499229/Operational_productivity_A.pdf (Accessed 6 July 2016).